Intensiﬁcation of Reutealis trisperma biodiesel production using infrared radiation: Simulation, optimisation and validation. (April 2019) - Silitonga, A.S.; Mahlia, T.M.I.; Kusumo, F.; Dharma, S.; Sebayang, A.H.; Sembiring, R.W.; Shamsuddin, A.H.
Abstract: Biodiesel production using intensification of methyl ester is becoming very important due to its considerably lower energy requirement and shorter reaction time in obtaining feedstock oil. The present study investigated utilisation of Reutealis trisperma oil to produce biodiesel. A Box-Behnken experimental design was used to optimise the transesterification process. The process variables were explored and the optimum methanol to oil molar ratio, catalyst concentration, reaction temperature, and reaction time were 8:1, 1.2 wt%, 64 °C and 68 min respectively and the corresponding methyl ester yield was 98.39%. The experiment was conducted in triplicate to validate the quadratic model. Results showed average methyl ester yield was 97.78%, which is close to the predicted value, indicating reliability of the model. Results also indicated that using infrared radiation method has many advantageous, such as less energy consumption as a result of deeper penetration of reactant mass which can improve mass transfer between the immiscible reactants in order to improve quality of biodiesel. The physicochemical properties of Reutealis trisperma methyl ester produced under optimum transesterification process variables were also measured and the properties fulfilled the fuel specifications as per ASTM D6751 and EN 14214 standards. Graphical abstract: Image Highlights: Reutealis trisperma oil is a non-edible vegetable oil with high free fatty acid content. Infrared radiation heated process was efficient productivity and less energy consumption. The transesterification parameters were optimised using Box-Behnken design. Good correlation between predicted (98.39%) and actual (97.78%) biodiesel yield. The obtained biodiesel complied with the ASTMD6751 and EN14214.